The Extended Access Created by the Capitalist Economy - Budhathoki, Drona; Sharma, Binod; Bhattarai, Teknath; Nyaupane, Ramji Prasad; Shrestha, Suresh (International Research Journal of MMC, 2023)
Capitalism is an economic and political system in which trade and industry are controlled by private owners for profit. Its core principles are: accumulation, ownership, and profiting from the capital. The study field was Dhankuta District, Mahalaxmi Municipality Ward no. 2. The principal objective of this article is to explore the extended access of the capitalist economy in the settlement of local communities. This study is based on a period of 10 years from January 2013 to September 30, 2023. In this study, primary data have been collected based on 42 households by census method. Interview schedule and observation method were used to carry out the process. The views of Chaitanya Mishra, Immanual Wallstein, Ian Carlos Fitzpatrick and Jagannath Adhikari have been included in the study. People here have spread to new places to worship like local market, Terai's Dharan, Itahari, Damak, Belbari, and Basbari Goldhap. This article contributes to a deeper understanding of economic systems, their impact on individuals and societies, and the potential for reform or transformation.